Costs of promoting cancer screening: Evidence from CDC's Colorectal Cancer Control Program (CRCCP). (June 2017) - Tangka, Florence K.L.; Subramanian, Sujha; Hoover, Sonja; Royalty, Janet; Joseph, Kristy; DeGroff, Amy; Joseph, Djenaba; Chattopadhyay, Sajal
Highlights: Three years of screening promotion expenditure data were analyzed. Many strategies implemented by the grantees were recommended by guidelines. Programs require additional guidance to use evidence-based promotion strategies. Abstract: The Colorectal Cancer Control Program (CRCCP) provided funding to 29 grantees to increase colorectal cancer screening. We describe the screening promotion costs of CRCCP grantees to evaluate the extent to which the program model resulted in the use of funding to support interventions recommended by the Guide to Community Preventive Services (Community Guide). We analyzed expenditures for screening promotion for the first three years of the CRCCP to assess cost per promotion strategy, and estimated the cost per person screened at the state level based on various projected increases in screening rates. All grantees engaged in small media activities and more than 90% used either client reminders, provider assessment and feedback, or patient navigation. Based on all expenditures, projected cost per eligible person screened for a 1%, 5%, and 10% increase in state-level screening proportions are 172, 34, and 17, respectively. CRCCP grantees expended the majority of their funding on Community Guide recommended screening promotion strategies but about a third was spent on other interventions. Based on this finding, future CRC programs should be provided with targeted education and information on evidence-based strategies, rather than broad based recommendations, to ensure that program funds are expended mainly on evidence-based interventions.